2016
DOI: 10.1371/journal.pone.0157404
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and Mitochondrial Dysfunction in Tenon Fibroblasts from Exfoliation Glaucoma Patients

Abstract: PurposeTo test the hypothesis that autophagy dysfunction is involved in exfoliation syndrome (XFS), a systemic disorder of extracellular elastic matrices that causes a distinct form of human glaucoma.MethodsFibroblasts derived from tenon tissue discards (TFs) from filtration surgery to relieve intraocular pressure in XFS patients were compared against age-matched TFs derived from surgery in primary open-angle glaucoma (POAG) patients or from strabismus surgery. Differential interference contrast light, and ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 56 publications
3
33
0
2
Order By: Relevance
“…For example, the marked downregulation of POMP (Figure 3), a ubiquitously expressed proteasome maturation protein in XFS tissues suggests a reduction of ubiquitin conjugating enzymes in XFS tissues 65 . Abnormalities in the closely related autophagy pathway have also been implicated in XFS 66 , a process that also involves ubiquitinproteasome signaling 67,68 . TMEM136 expression was predominantly localized to vascular endothelia.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the marked downregulation of POMP (Figure 3), a ubiquitously expressed proteasome maturation protein in XFS tissues suggests a reduction of ubiquitin conjugating enzymes in XFS tissues 65 . Abnormalities in the closely related autophagy pathway have also been implicated in XFS 66 , a process that also involves ubiquitinproteasome signaling 67,68 . TMEM136 expression was predominantly localized to vascular endothelia.…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro study using fibroblast cells excised from Tenon's capsule of XFS and POAG patients during filtration surgery and strabismus surgery showed that, compared to POAG counterparts, Tenon's cells from XFS patients had different phenotypic signs of reduced clearance of autophagosomes due to autophagy dysfunction (Want et al. ). In a following in vitro study, it was shown that those functional and structural differences were statistically significant between POAG and XFS‐derived Tenon capsule fibroblasts (Wolosin et al.…”
Section: Dysfunction Of Protein‐aggregate Clearance: Autophagymentioning
confidence: 99%
“…Non‐functioning mitochondria have been observed in XFS in vitro models, which could reduce the efficiency of respiration, leading to reduced ATP with increased reactive oxygen species production (Want et al. ). During ageing, some ATG s are downregulated and autophagy function declines in humans, which is believed to be linked with age‐related disease (Leidal et al.…”
Section: Dysfunction Of Protein‐aggregate Clearance: Autophagymentioning
confidence: 99%
See 2 more Smart Citations